Entitlement to Substantive Due Process: Old Versus New Property in Land Use Regulation - Daniel R. Mandelker (Washington University Journal of Law & Policy, 2000)
This Essay examines an important rule that bars a substantive due process action when a landowner claims that a municipality has arbitrarily denied a development approval. This rule holds that a landowner cannot challenge the denial unless he has an entitlement to the approval.
Keywords: Due process of law; Land use; Regulatory taking (Law)